2007
DOI: 10.1158/1055-9965.epi-07-0176
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin E Levels and Risk of Lymphoma in a Case-Control Study in Spain

Abstract: Epidemiologic studies have shown an inverse association between atopy and malignant lymphoma, but results are inconsistent. We investigated levels of IgE, before and after commencement of treatment, and evaluated lymphoma risk in relation to total and specific IgE levels. Serum levels of IgM, IgA, and IgG were also measured. We enrolled 467 newly diagnosed lymphoma cases and 544 hospital controls, matched for age, sex, and hospital. Lymphomas were histologically confirmed and categorized according to the WHO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 45 publications
(46 reference statements)
5
38
0
Order By: Relevance
“…Moreover, high levels of IgE and atopy do not always correlate with clinically recognized allergies, placing qualifications of any equivalence of IgE and recounted history of allergy. To better define the association between atopy and cancer, some recent studies have analyzed the association between IgE levels and cancer diagnosis [24][25][26][27][28][29][30], although all such studies were also case-control studies in which the validity is much dependent on the method of selection controls [8,27]. As a consequence of the case-control design, all IgE measurements were taken after tumor diagnosis and only two studies reported IgE measurements taken before treatment initiation [26,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high levels of IgE and atopy do not always correlate with clinically recognized allergies, placing qualifications of any equivalence of IgE and recounted history of allergy. To better define the association between atopy and cancer, some recent studies have analyzed the association between IgE levels and cancer diagnosis [24][25][26][27][28][29][30], although all such studies were also case-control studies in which the validity is much dependent on the method of selection controls [8,27]. As a consequence of the case-control design, all IgE measurements were taken after tumor diagnosis and only two studies reported IgE measurements taken before treatment initiation [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…Five of seven studies used random controls selected via, for instance, random digit dialing (n = 2) or from general health surveys [24][25][26][27][28]. Two studies used hospital-based controls seen in the hospital for a diagnosis distinct from the cancer outcome of interest [29,30]. The methods used to measure IgE are described in Table 1.…”
Section: Meta-analysismentioning
confidence: 99%
“…31 The alterations of cellular and/or humoral immunity in NHL patients are not uncommon. 32 This study shows that there was a decrease in serum levels of both IgM and IgA in patients with NHL while the level of IgG was increased but did not reach a significant level. In agreement with this study, two reports showed that IgM and IgA were also decreased in patients with NHL.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresismentioning
confidence: 59%
“…In agreement with this study, two reports showed that IgM and IgA were also decreased in patients with NHL. 32,33 IgG levels were not decreased in one study, 32 but in contrast, it was decreased in other studies, 33 while a study 34 showed no increase in IgG levels, and lower IgG levels in NHL patients was observed. 33,34 Levels of all immunoglobulin class were decreased in NHL patients.…”
Section: Frequency Of M Bands Showed By Serum Protein Electrophoresismentioning
confidence: 68%
See 1 more Smart Citation